EKSISTENSI DAN INTEGRITAS BAWASLU DALAM PENANGANAN SENGKETA PEMILU - Muhammad Ja’far (FAKULTAS HUKUM UM PAREPARE, 2019)
As an institution that is presented to oversee the implementation of elections, the General Election Supervisory Board is expected the role and integrity so that the implementation of elections can run as expected and running smoothly. The formulation of the issues raised is how the role of Election Supervisory Body in handling election disputes in Indonesia. The research method used is juridical normative with primary law material. The result of the research is that the Election Supervisory Board has an important role as the guard of the general election as mandated in the Law on the Implementation of General Election, it is mentioned that the function of Election Supervisor is as described in the duties, authorities and obligations of General Election Supervision